2020
DOI: 10.1161/jaha.119.015975
|View full text |Cite
|
Sign up to set email alerts
|

Priorities for Patient‐Centered Research in Valvular Heart Disease: A Report From the National Heart, Lung, and Blood Institute Working Group

Abstract: Over the past decade, the field of valvular heart disease ( VHD ) has rapidly transformed, largely as a result of the development and improvement of less invasive transcatheter approaches to valve repair or replacement. This transformation has been supported by numerous well‐designed randomized trials, but they have centered almost entirely on devices and procedures. Outside this scope of focus, however, myriad aspects of therapy and management for patients with VHD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…Stressing the importance of matching research efforts to patients' complex and diverse journeys of care, the consensus recommendations strongly endorsed the pressing need to inform research focused on SDM and PROMs across the continuum of care (Figure 3). 46 This leadership illustrates current opportunities to continue to narrow the gap between the rapid innovation in the management of valvular heart disease and patients' perspectives of the care we provide.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Stressing the importance of matching research efforts to patients' complex and diverse journeys of care, the consensus recommendations strongly endorsed the pressing need to inform research focused on SDM and PROMs across the continuum of care (Figure 3). 46 This leadership illustrates current opportunities to continue to narrow the gap between the rapid innovation in the management of valvular heart disease and patients' perspectives of the care we provide.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“… 3 , 4 Accordingly, beyond replacing the heart valve, there is growing recognition that targeting frailty and impaired physical function is important to optimize patient-centred outcomes. 5 A recent report on cardiac rehabilitation (CR) after valve surgery showed that although CR was associated with reduced rehospitalization and mortality in the first year after the surgery, participation rates were only 43%. 6 While the literature demonstrates similar associations between CR and reduced mortality among patients treated for coronary artery disease, rates of participation are even lower.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of the most appropriate intervention (transcatheter or surgical) depends on the person’s risk profile 3 and their individual preferences. 12 If a person is not deemed ready or eligible for an intervention, they are put on active surveillance. A ‘watch and wait’ approach is taken, 3 with the understanding that regular reviews, including echocardiograms, are needed to make sure patients can be offered heart valve replacement or repair should their condition deteriorate.…”
Section: Timely Interventionmentioning
confidence: 99%
“…Ongoing collection of patient-reported outcomes data can ensure clinical teams are aware of the psychological and quality-of-life status of their patients over time and can offer tailored support accordingly. 12 …”
Section: Addressing the Psychological Dimension Of Receiving A Diagnosis Of Heart Valve Diseasementioning
confidence: 99%
See 1 more Smart Citation